Microfilaria in forearm swelling aspirate: An unusual finding - Shastry Srikanth (Wolters Kluwer Medknow Publications, 2014)
Filariasis is a major public health problem in tropical countries, including India. The disease is endemic all over India, especially in Uttar Pradesh, Bihar, Jharkhand, Andhra Pradesh, Orissa, Tamil Nadu, Kerala, and Gujarat. A majority of infected individuals in filarial endemic communities are asymptomatic. Adult worms live in the lymphatic vessels of the definitive host and microfilaria is released and circulates in the peripheral blood. Cases of microfilaremia have been reported from atypical sites such as thyroid, lymph node, pleural and pericardial fluid, breast lump, and bone marrow. We here present a case of microfilaria in the forearm swelling found on fine-needle aspiration cytology, which is an unusual finding.